Blurring Boundaries: Literary Journalism and Political Performance in B.P. Koirala’s Atmabrittanta: Late Life Recollections - Mukhiya , Narendra Man (Bon Voyage, 2025)
This paper analyzes B.P. Koirala’s Atmabrittanta: Late Life Recollections from the perspectives of literary journalistic discourse which blurs the boundary between literary and journalistic writing thereby giving a political message such as the notion of nation-state that depends on both people and geography. Literary journalism is a form of newspaper writing that blends facts and fictions. It goes beyond answering the informational questions, and showcases events, and affairs with political overtones. Koirala’s text is unique one that blends history, personal narratives, and national issues. Koirala’s writing eschews the formula of newspaper feature writing with its predictability of future along with dealing with fixity of history as constructed narrative. He combines elements of realistic fiction and factual details to portray daily life. This paper attempts to examine the literary journalistic features that capture the essence of the contemporary life of Koirala’s time. In doing so, the combination of literature and journalism best understands the contemporary society. Drawing on John Hellmann and Sonja Merljak Zdovc’s ideas of literary journalism and highlighting how literary journalistic writings depict reality of society based on fact and fiction, the paper argues that literary journalism expresses the facts and envisions political theme associated with these facts.